Association Between Pharmacological Treatment Regimens and Quality of Life Among Rural Type 2 Diabetic Patients: A Comparative Analysis in Eastern China - Sihan Li MPA; Su Zhao MPA; Lizhu Wang MPA; Xian Wu MPA; Zinan Zhang PhD; Zhonghua Wang PhD (SAGE Publishing, 2024)
Numerous studies have explored the relationship between pharmacological treatment regimens and the quality of life (QoL) of type 2 diabetes (T2D) patients. However, there is a dearth of comparative studies focusing on the QoL among rural T2D patients in China across 3 distinct pharmacological treatments: oral antidiabetic drugs (OADs), insulin therapy, and a combination of OADs and insulin. Additionally, the specific correlation between these treatment regimens and distinct dimensions of QoL remains unclear, necessitating further investigation. Data from a survey of rural T2D patients in eastern China were analyzed to calculate QoL scores for different treatment groups. Multivariate linear regression was then used to assess variations in overall QoL and specific dimensions among patients on OADs, insulin, and combined therapy. OADs were most commonly used (70.36%), followed by combined (19.47%) and insulin therapy (10.17%). Patients on OADs reported the highest overall QoL, with reduced physical discomfort, improved psychological well-being, enhanced treatment satisfaction, and fewer medication side effects. Conversely, those on combined therapy had the lowest overall QoL, primarily due to increased physical discomfort. Insulin users had moderately positive overall QoL but lower psychological well-being and treatment satisfaction, along with more adverse reactions. Disparities in QoL and its dimensions exist among rural T2D patients based on treatment regimens. Healthcare providers should prioritize support systems and interventions to help patients manage side effects of insulin and combined therapy, thereby improving their QoL.